Penyuluhan Pelaporan Keuangan Berbasis Pemberdayaan Kelompok Wanita Tani - Aprih Santoso; Sri Yuni Widowati; Saifudin Saifudin (IAHN Gde Pudja Mataram, 2022)
PkM aims to disseminate science and technology and at KWT Ceria Pagersari Village, Patean District, Kendal Regency so that members of the Ceria Women Farmers Group can prepare financial reports correctly. It is hoped that the results of this PkM are that members of the Ceria Women Farmers Group will be able to understand financial statements and be able to prepare financial reports for the Women Farmers Group. The PkM technique uses extension techniques by presenting the material by the PkM team at the Faculty of Economics, University of Semarang (USM). Besides that, discussions were also held with members of the Ceria Women Farmers Group by the PkM Team of the USM Faculty of Economics. Feedback is done through filling out a list of questions. As a result, the realization of the PkM on the presentation of the material face-to-face and through filling out the list of questions has shown that the members of the Ceria Women Farmers Group have said that the PkM goals have been realized, because the Ceria Women Farmers Group members have benefited, namely the increase in skills related to report generation. finance. The Ceria Women Farmer's Group, Pagersari Village, Patean District, Kendal Regency, has been able to independently prepare its financial reports.